Diagnosed Incidentally by Duodenal Biopsy - Kevin Groudan MD; Kamesh Gupta MD; Jean Chalhoub MD; Rohit Singhania MD (SAGE Publishing, 2021)
Giardia lamblia (also referred to as Giardia intestinalis and Giardia duodenalis ) is the most common intestinal parasite in the world, affecting approximately 200 million people annually. Symptoms of Giardia include foul-smelling diarrhea, abdominal cramping, bloating, gas, and nausea. Although usually self-limiting, Giardia can progress to dehydration, malnutrition, and failure to thrive, especially in immunocompromised individuals. Early diagnosis and treatment is imperative to prevent and control infection of Giardia . Infectious Disease Society of America diagnostic guidelines recommend obtaining stool studies to diagnose Giardia ; when stool studies are negative but suspicion remains high, duodenal aspirate microscopy is the only alternative diagnostic strategy suggested. We report a patient diagnosed incidentally with Giardia from a duodenal biopsy specimen obtained during a workup for a gastrointestinal bleed. There are limited cases of Giardia diagnosed by duodenal biopsy reported in the literature. We review studies that suggest duodenal biopsy can be a very sensitive strategy for the diagnosis of Giardia .